Autofocus and motion error compensation methods for gantry machine in ultra-precise laser machining applications - Piscalov Artur; Mikulis Giedrius; Rafanavicius Vytautas (EPJ Web of Conferences)
Error compensation by applying motion control methods makes auto-focus easy and reliable in micro-machining applications. We present a method for dynamic roll and yaw compensation in gantry machines.